A low-profile low-power converter with coreless PCB isolation transformer. - Tang, S.C (IEEE Transactions on power electronics)
Very small manually wound transformers for sub-watt DC-DC converters are notorious for their relatively high cost and low reliability. In this paper, an isolated low-profile low-power 8 MHz soft-switching power converter using a coreless printed circuit board (PCB) transformer is described. Coreless PCB transformers eliminate several problems of their core-based counterparts in low-power applications. The diameter of the coreless PCB transformer is merely 0.46 cm. The converter's power output is about 0.5 W with a typical transformer efficiency of 63%. The high-frequency capability, high reliability and the low-profile structure make coreless PCB transformers a viable and attractive option for reliable mega-hertz switching converters and micro-circuits